2018
DOI: 10.1177/1534508418796271
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Validity and Diagnostic Accuracy of a Reading Computer-Adaptive Test

Abstract: Universal screening is the first mechanism by which students are identified as at risk of failure in the context of multitiered systems of supports. This study examined the validity and diagnostic accuracy of a reading computer-adaptive test as a screener to identify state achievement test performance for third through fifth graders ( N = 1,696). Single time points and slopes within year and longitudinally were examined. Validity results for single points were moderate (.60–.79, p < .002). Validity for slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In a comparison of CBM and CATs, SM was found to be a significant predictor of performance on a statewide test (Shapiro & Gebhardt, 2012). Expanding on Shapiro and Gebhardt (2012), Ochs et al (2016) investigated the diagnostic accuracy of SR and performance on a statewide achievement test. The results found that SR displayed moderate to high levels of diagnostic accuracy (Ochs et al, 2016).…”
Section: Cats As Universal Screenersmentioning
confidence: 99%
See 3 more Smart Citations
“…In a comparison of CBM and CATs, SM was found to be a significant predictor of performance on a statewide test (Shapiro & Gebhardt, 2012). Expanding on Shapiro and Gebhardt (2012), Ochs et al (2016) investigated the diagnostic accuracy of SR and performance on a statewide achievement test. The results found that SR displayed moderate to high levels of diagnostic accuracy (Ochs et al, 2016).…”
Section: Cats As Universal Screenersmentioning
confidence: 99%
“…Expanding on Shapiro and Gebhardt (2012), Ochs et al (2016) investigated the diagnostic accuracy of SR and performance on a statewide achievement test. The results found that SR displayed moderate to high levels of diagnostic accuracy (Ochs et al, 2016). Last, more recent research supports the validity of SR as a predictor of performance on a state test (Ochs et al, 2020).…”
Section: Cats As Universal Screenersmentioning
confidence: 99%
See 2 more Smart Citations